Fruit From Two Kiwifruit Genotypes With Contrasting Softening Rates Show Differences in the Xyloglucan and Pectin Domains of the Cell Wall - Fullerton, Christina G.; Prakash, Roneel; Ninan, Annu Smitha; Atkinson, Ross G.; Schaffer, Robert J.; Hallett, Ian C.; Schröder, Roswitha (Frontiers in Plant Science, 2020)
Fruit softening is controlled by hormonal and developmental cues, causing an up-regulation of cell wall-associated enzymes that break down the complex sugar matrices in the cell wall. The regulation of this process is complex, with different genotypes demonstrating quite different softening patterns, even when they are closely related. Currently little is known about the relationship between cell wall structure and the rate of fruit softening. To address this question, the softening of two Actinidia chinensis var. chinensis (kiwifruit) genotypes (a fast ‘AC-F’ and a slow ‘AC-S’ softening genotype) was examined using a range of compositional, biochemical, structural and molecular techniques. Throughout softening, the cell wall structure of the two genotypes was fundamentally different at identical firmness stages. In the hemicellulose domain, xyloglucanase enzyme activity was higher in ‘AC-F’ at the firm unripe stage, a finding supported by differential expression of xyloglucan transglycosylase/hydrolase genes during softening. In the pectin domain, differences in pectin solubilization and location of methyl-esterified homogalacturonan in the cell wall between ‘AC-S’ and ‘AC-F’ were shown. Side chain analyses and molecular weight elution profiles of polyuronides and xyloglucans of cell wall extracts revealed fundamental differences between the genotypes, pointing towards a weakening of the structural integrity of cell walls in the fast softening ‘AC-F’ genotype even at the firm, unripe stage. As a consequence, the polysaccharides in the cell walls of ‘AC-F’ may be easier to access and hence more susceptible to enzymatic degradation than in ‘AC-S’, resulting in faster softening. Together these results suggest that the different rates of softening between ‘AC-F’ and ‘AC-S’ are not due to changes in enzyme activities alone, but that fundamental differences in the cell wall structure are likely to influence the rates of softening through differential modification and accessibility of specific cell wall polysaccharides during ripening.